Is the athlete or the equipment? An analysis of the top swim performances from 1990 to 2010 - O'Connor, L. M.; Vozenilek, J. A. (The Journal of Strength and Conditioning Research, 2011)
Forty-three world record swims were recorded at the 2009 Fédération Internationale de Natation (FINA) World Championship meet in Rome. Of the 20 FINA recognized long-course (50-m pool) swimming events, men set new world records in 15 of those events, whereas women did the same in 17 events. Each of the men's world records and 14 of the 17 women's records still stand. These performances were unprecedented; never before had these many world records been broken in such a short period of time. There was much speculation that full-body, polyurethane, technical swimsuits were the reason for the conspicuous improvement in world records. Further analysis led the FINA to institute new rules on January 1, 2010, that limited the types of technical swimsuits that could be worn by athletes. No long-course world record has been broken since then. We sought to understand this phenomenon by analyzing publicly available race data and exploring other possible causes including improvements in other sports, improvements in training science, changes in rules and regulations, gender differences, anaerobic vs. aerobic events, unique talent, and membership data.